SERAPAN P DAN PERTUMBUHAN TANAMAN JAGUNG (Zea mays L.) DENGAN PEMBERIAN BEBERAPA JENIS DAN KOMBINASI BAHAN ORGANIK PADA SISTEM IRIGASI TETES - Lorinanggarani, Ray Harmida; Arifin, Zaenal; Bustan, Bustan; Kusnarta, I Gusti Made; Suriadi, Ahmad (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2024)
The objective of this research ia to know the uptake of P and growth of maize (Zea mays L.) as a result of the application of several types and combinations of organic materials using a drip irrigation system. This research used a randomized block design with 6 treatments and 3 replications: B0 (No Organic Material), B1 (10 tons/ha Manure), B2 (10 tons/ha Biochar), B3 (10 tons/ha Vermicompost), B4 (4.5 tons/ha Biochar + 4.5 tons/ha Vermicompost), B5 (4.5 tons/ha Biochar + 4.5 tons/ha Manure). The research results showed that the combination of organic materials and their combinations had a significant effect on P-Available soil, P-Total soil, Plant Height, Number of Leaves and Leaf Width. The application of organic material had no significant effect on soil pH and P uptake. The best treatment in this study was B1 treatment (10 tons/ha of Manure. The best combination in this study was B5, namely B5 (4.5 tons/ha Biochar + 4.5 tons/ha Manure).